Which stretching instruction should be given to assess joint maximal range of motion?. (July 2022) - Radaelli, Régis; Freitas, Joana; Almeida, Nuno; Vaz, João R.; Freitas, Sandro R.
Abstract: This study aimed to determine the intra-day reliability, individuals performance expectancy, and biomechanical response of nine stretching instructions in assessing the maximal range of motion (mROM) during the passive ankle dorsiflexion test. Twenty healthy young participants were tested in two sessions within the same day. Nine stretching instructions composed by intensity-domain (i.e. minimum, point, and maximum) and sensation-domain (i.e. tolerance, discomfort, and pain) words were used to impose plantar flexors stretching. In the first session, individuals were requested to order the nine stretching instructions in ascending order. The ankle joint torque-angle and medial gastrocnemius, soleus and tibialis anterior electric activity were assessed in both sessions. A moderate to high reliability was observed across instructions (ICC = 0.65–0.87). Most stretching instructions showed high intra-day reliability outcomes, where discomfort and tolerance showed moderate reliability. 70% of individuals performed the stretching maneuvers consistently to stretching instructions performance expectancy. A greater torque-angle response was observed for the instructions involving the word pain (ROM = 40.5 ± 1.6°), compared to discomfort (29.5 ± 1.8°), and tolerance (30.5 ± 2.0°) that produced similar stretching intensities. Instructions involving the terms minimum (29.6 ± 2.0°), point (33.3 ± 7.6°), and maximum (37.6 ± 7.2°) were more discriminative of stretching intensities than sensation-domain terms. In conclusion, stretching instructions targeting the joint maximal range of motion produce different joint torque-angle responses and they may not be understandable by all individuals, although (in general) they can be used reliably .